(untitled) (University of Khartoum Engineering Journal, 2022)
The hydrological features of Wadis in arid and semi-arid regions are unique. The hydrological regime is characterized by high variability in temporal and spatial rainfall distributions, flash floods, absence of base flow in most cases, and high rates of evapotranspiration. There have been many efforts to estimate, analyse and predict the stream flow in Wadis either for water harvesting or flood control. The aim of this paperis to develop simulation model fora semi-arid basin in Sudan, using Hydrologic Modelling System of the Hydrologic Engineering Center(HEC-HMS)software, developed by the US Army Corps of Engineers. The HEC-HMS modelling was done in conjunction with the HEC-GeoH MS extension in Arc Map. The aridity index of United Nations Environment (UNEP), which is one of the most adopted indices, was used to estimate the aridity of the study area. Analysis of the rainfall records at stations with automatic gauges had shown that there is a similarity in the shape of the incremental rainfall depths hyetographs, for a particular climatic region. Accordingly, a new procedure for transforming the daily rainfall depths into incremental rainfall depths hyetographs, is developed. These incremental rainfall depths hyetographs and the corresponding single flood events in Wadi AbuFargha basin, were modelled using HEC-HMS. The results showed a very good similarity between the observed and the simulated flows. Nash and Sutcliffe efficiency criterion was used to evaluate the model performance. The overall model efficiencies were 92% and 88%, in the calibration and verification periods, respectively. Therefore, it is concluded that the HEC-HMS software offers a reliable tool for flash flood forecasting in data scare semi-arid regions.